2019
DOI: 10.1021/acs.jpcc.8b08890
|View full text |Cite
|
Sign up to set email alerts
|

Redox Behavior of Pt/Co3O4(111) Model Electrocatalyst Studied by X-ray Photoelectron Spectroscopy Coupled with an Electrochemical Cell

Abstract: Achieving high stability of supported noble metal nanoparticles with respect to sintering is one of the major challenges in electrocatalysis. In this study, we explored the role of metal–support interaction in stabilizing the morphology of a well-defined model electrode consisting of Pt nanoparticles supported on well-ordered Co3O4(111) films on Ir(100). We employed X-ray photoelectron spectroscopy coupled with an electrochemical cell to analyze changes in the oxidation states of both the supported Pt nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Transition-metal (oxy)hydroxides have been shown to be highly active for the oxygen evolution reaction (OER), and iron specifically is hypothesized to be involved in the active site on several mixed oxides. [44][45][46][47] The formation of (oxy)hydroxides under OER conditions has been described for several systems, [48][49][50][51][52][53][54][55] and the first direct atomic-scale study of such a system was recently published by Fester et al, who used STM and XPS to show that exposure to ambient pressures of water transforms monolayer CoO x films supported on Au(111) to a cobalt (oxy)hydroxide. 15 However, the present work is the first time the conversion to (oxy)hydroxide structures have been imaged at an atomic scale on a bulk oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Transition-metal (oxy)hydroxides have been shown to be highly active for the oxygen evolution reaction (OER), and iron specifically is hypothesized to be involved in the active site on several mixed oxides. [44][45][46][47] The formation of (oxy)hydroxides under OER conditions has been described for several systems, [48][49][50][51][52][53][54][55] and the first direct atomic-scale study of such a system was recently published by Fester et al, who used STM and XPS to show that exposure to ambient pressures of water transforms monolayer CoO x films supported on Au(111) to a cobalt (oxy)hydroxide. 15 However, the present work is the first time the conversion to (oxy)hydroxide structures have been imaged at an atomic scale on a bulk oxide.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, it was demonstrated that model electrocatalysts based on Co 3 O 4 (111) thin films can be prepared and transferred into an EC environment while maintaining atomic-level control. ,, Recently, we identified the EMSI between nanometer-sized Pt particles and Co 3 O 4 (111) by means of ex situ emersion X-ray photoelectron spectroscopy (XPS) . In the subnanometer regime, however, Pt particles show different particle size effects and different chemical behavior. …”
mentioning
confidence: 99%
“…Two spin–orbit doublets emerge in the Pt 4f spectra of as-prepared conventional Pt NPs at 71.5 (Pt 4f 7/2 ) and 72.3 eV (Pt 4f 7/2 ) which are associated with metallic Pt 0 and a partially oxidized Pt δ+ species at the metal/oxide interface, respectively. , In contrast to conventional NPs, no metallic Pt 0 was detected in the Pt 4f spectra of the subnanometer Pt aggregates. Instead, two spin–orbit doublets emerge at 72.4 (Pt 4f 7/2 ) and 73.9 eV (Pt 4f 7/2 ) associated with partially oxidized Pt δ+ and Pt 4+ species, respectively. , The absence of metallic Pt 0 suggests that EMSI leads to a modification of the electronic structure of all Pt atoms within the subnanometer particles (see Supporting Information, Chapter 3.1 for a more detailed discussion on the growth mode).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found an interface Pt oxide which is stable between 0.5 and 1.4 V and believed this to be the reason for the catalyst's high stability towards particle sintering. 39 Studies on model electrodes made from doped-SnO 2 thin films supporting Pt nanoparticles showed that electronic metal-support interactions are the cause for superior specific ORR activity when compared to Pt on carbon. 40,41 Recently, we showed that the density of oxidizable Pt sites is an important property governing catalytic activity for ORR as we investigated the degradation pathways of ITO-supported Pt nanoparticles under simulated fuel cell conditions using combined in situ X-ray diffraction and scattering techniques.…”
Section: Introductionmentioning
confidence: 99%